The non-nuclear DifB NF-κB isoform affects courtship, circadian, and locomotor behavior in adult Drosophila melanogaster - Wijesekera, Thilini P.; Stephens, Nicole P.; Hingnekar, Aniket; Gedamu, Hanna Y.; Dezso, Natalie R.; Strange, Madison; Risbud, Saee M.; Dinh, Alexander D.; Atkinson, Nigel S. (Frontiers in Behavioral Neuroscience, 2025)
The Drosophila Dif gene uses alternative messenger RNA (mRNA) processing to encode two different nuclear factor kappa Bs (NF-κBs). The DifA isoform is a canonical NF-κB transcription factor that is important for activation of the immune response. Our primary interest is the DifB isoform, which is neuron-specific and expressed in the mushroom bodies and antennal lobes of the adult brain. The DifB protein lacks a nuclear localization signal and does not enter the nucleus. Instead, it localizes to the cell body surrounding the nucleus, to axonal-dendritic projections, and to the synapse. DifB is an unusual member of the NF-κB superfamily, as it acts outside the nucleus to modulate behavior. The DifB isoform has been shown to modulate the sensitivity of the adult to sedation by alcohol. Here, we conducted a survey to determine whether the DifB NF-κB is important for other fly behaviors. We observed that a DifB-specific mutation strongly suppresses male courtship. However, despite the expression of DifB in the mushroom bodies, a DifB null allele does not interfere with learning in a learned-suppression-of-phototaxis assay. Finally, both DifA-specific and DifB-specific mutations caused flies to have a circadian long rhythm phenotype, although the circadian phenotype cannot be scored in male DifB mutants because of a sexually dimorphic locomotor defect.